The Eastern Enlargement of the EU - An Initial Assessment: Growing Imports to the New Member States from the Euro Zone - Timo Baas; Mechthild Schrooten (Weekly Report, 2005)
On 1 May 2004 eight former socialist countries - Estonia, Latvia, Lithuania, Poland, the Czech Republic, the Republic of Slovakia, Hungary and Slovenia - joined the European Union. In the accession year the new EU member states have experienced powerful macroeconomic dynamics, and convergence of per capita income within the new EU-25 was progressing. However, it is remarkable that, for the accession countries, the eastern enlargement of the EU had not the particularly strong impact on growth for the accession countries that many had expected - macroeconomic growth decreased in many of the new member states in the period after entry, although it is still high. This is probably due to stronger trade links which developed between the euro-zone countries and the new member states after their accession. Whereas the new member states were confronted with relatively weak demand from the euro zone, the euro-zone countries in turn could profit from the dynamic development in the new member stat
Keywords: 330